Koloradska planota in kanjonske pokrajine jugovzhodnega Utaha - Kunaver, Jurij (Geografski obzornik, 2002)
The author describes the Utah part of Colorado plateau which is intensely dissected by a branched river system of the Coloradom, its central section and the upper reaches in particular, and two of its tributaries, the Green River and the San Juan. The area is geologically rather evenly composed of 2400 meters thick Cambrium to Tertiary sediment layer which is dissected by numerous rivers to different depths, most deeply in the Great Colorado Canyon. Therefore, it is unique for the study of its extremely long-lasting geological and geomorphological developments.
Keywords: geologija; geomorfologija; Kolorado; relief; Utah; ZDA